2021
DOI: 10.12973/ijem.7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Digital Literacy Levels and Technology Integration Competence of Turkish Academics

Abstract: <p style="text-align:justify">Today’s individuals are expected to have skills in many areas as a natural consequence of the advances that have been taking place in society and technology. Particularly in developed countries, these skills are also called 21<sup>st</sup> century skills. Critical, creative and reflective thinking, problem solving and keeping up with the digital age (digital literacy) are some of these skills. Universities play a significant role in raising qualified individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…With good digital literacy skills, students will easily read and access features contained in digital technology that make them feel like they receive a reward, for example, when playing games, getting information as expected or communicating via online with other people (Feinstein, 2011). The results showed that age and grade level variables created significant differences in academic digitization (Ayyildiz et al, 2021). It is necessary to identify digital readiness in teachers so that learning can be maximized (Peled, 2021).…”
Section: International Journal Of Instructionmentioning
confidence: 98%
“…With good digital literacy skills, students will easily read and access features contained in digital technology that make them feel like they receive a reward, for example, when playing games, getting information as expected or communicating via online with other people (Feinstein, 2011). The results showed that age and grade level variables created significant differences in academic digitization (Ayyildiz et al, 2021). It is necessary to identify digital readiness in teachers so that learning can be maximized (Peled, 2021).…”
Section: International Journal Of Instructionmentioning
confidence: 98%
“…Akan tetapi suatu keniscayaan bagi pengelola untuk terus memeroleh keuntungan jika kompetensi yang melekat padanya mampu menempatkan suatu reaksi adaptif selaras tuntutan perkembangan pariwisata. Esensi dari reaksi tersebut tentu bermuara pada eksistensi kompetensi yang terus mendukungnya mempertahankan atau meraih prestasi gemilang dalam bidang yang digeluti, termasuk kompetensi literasi digital (Ayyildiz, Yilmaz, & Baltaci, 2021;Radovanović et al, 2020).…”
Section: Pendahuluanunclassified
“…However, every student can survive and prosper if the skill aligned with it can elicit an adaptive response that is compatible with the demands of the working world. The essence of this reaction is undoubtedly the presence of competencies that continue to assist him/her in achieving brilliant accomplishments in his/her career, including digital literacy competencies [35], [36].…”
Section: Concept Of Digital Literacy Competencementioning
confidence: 99%